DAMPAK PROGRAM KAMPUS MENGAJAR TERHADAP HASIL NILAI LITERASI DAN NUMERASI SEKOLAH SERTA BUDAYA LITERASI SISWA - Nugraha, Muhamad Aditia; Zidane, Rizky Akhmad; Hamdan, Ahmad (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Merdeka Belajar Kampus Merdeka (MBKM) program was launched by the government through the Kementerian Pendidikan Tinggi, Riset, dan Teknologi (Diktiristek) as a form of assistance to schools that still have deficiencies. This initiative is designed to address the challenges faced by every UPTD. The main focus of this service is to assess the effectiveness of Kampus Mengajar programs in improving school literacy and numeracy and student literacy culture at SMP Negeri 21 Tasikmalaya. This study uses descriptive qualitative research techniques to present the observed facts methodically. Data collection is done by observation, interview and documentation. The process of improving literacy, numeracy and literacy culture of students is carried out through innovation programs held by teaching campus students, namely: (1)literacy education with West Java reading ambassadors, (2)mobile library visits, (3)reading terraces (4)mading renewal, (5)fan math, and (6)literacy classes. The results showed that the program "Kampus Mengajar" has a positive impact on improving literacy, numeracy and literacy culture of students. The students showed an increase in enthusiasm in program activities, especially through their interaction with the students participating in the batch 6 Kampus Mengajar